2005
DOI: 10.1097/00001199-200503000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Productive Work and Employment for Persons With Traumatic Brain Injury

Abstract: This article describes return to work outcomes for individuals with traumatic brain injury (TBI) through a selective review of the published literature and an examination of TBI labor force participation from the Rehabilitation Services Administration 91l and the Social Security Administration Benefits Planning, Assistance and Outreach databases. Implications and recommendations to further our understanding about the different parts of the work outcome profile of individuals with TBI are offered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
93
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(97 citation statements)
references
References 35 publications
3
93
1
Order By: Relevance
“…A review of biennial Rehabilitation Service Administration 911 data from 1993 to 2001 indicated that the vocational rehabilitation system is serving increasing numbers of individuals with ABI with some success. However, the data indicate that only 10 percent were rehabilitated using supported employment [24].…”
Section: Return-to-work Intervention Strategies and Issuesmentioning
confidence: 97%
See 2 more Smart Citations
“…A review of biennial Rehabilitation Service Administration 911 data from 1993 to 2001 indicated that the vocational rehabilitation system is serving increasing numbers of individuals with ABI with some success. However, the data indicate that only 10 percent were rehabilitated using supported employment [24].…”
Section: Return-to-work Intervention Strategies and Issuesmentioning
confidence: 97%
“…Using this approach, the individual does not have to "get ready" to work. Instead, customized employment support is provided by a vocational rehabilitation professional, sometimes called a job coach or employment specialist [22][23][24][25][26].…”
Section: Return-to-work Intervention Strategies and Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Persons with moderate to severe trauma have an unemployment rate around 75 percent, probably because of problems with cognition, loss of insight into impairments, and challenges with interpersonal skills, which are all more frequent as severity of TBI increases [43][44]. Recent observations on polytrauma suggest that having more than one disability creates a "burden of adversity" that results in greater depletion of personal resources than a single disability [45].…”
Section: Dual Diagnosis Of Traumatic Brain Injury and Spinal Cord Injurymentioning
confidence: 99%
“…Although most individuals with mild to moderate TBI histories recover from these postconcussive symptoms within days to weeks [17][18], as many as 10 to 20 percent suffer from persistent postconcussive symptoms that do not resolve within this time frame [19]. These symptoms can hamper the successful reintegration of Veterans with a history of TBI by limiting the functional recovery required for community reintegration [20][21].…”
Section: Introductionmentioning
confidence: 99%